2013
DOI: 10.1149/05002.0313ecst
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Hydrogen Mass Transport Coefficients in a PEMFC at Different Operating Conditions Using a Hydrogen Pump Configuration

Abstract: A proton exchange membrane fuel cell system (PEMFCS) operated electroytically at its limiting current was proposed previously as a technology to separate H 2 and He through the electrochemical oxidation of H 2 . In this work the fraction of H 2 remaining in the effluent of two different sized PEMFCs with different flow field designs was studied at several operating conditions which included different: system temperatures, inlet relative humidity (R.H.), and system pressures to determine the most efficient oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous work demonstrated that a PEMFC operated as an electrolytic cell at the limiting current could attain outlet streams with less than 50 parts per million (ppm) H 2 by controlling the flow rate of gases in the feed (1). The fuel cell operating conditions that resulted in the greatest He purity were also identified (2). However, the effects of continuous operation for an extended duration on the fraction of H 2 removed by the PEMFC (i.e.…”
mentioning
confidence: 99%
“…Previous work demonstrated that a PEMFC operated as an electrolytic cell at the limiting current could attain outlet streams with less than 50 parts per million (ppm) H 2 by controlling the flow rate of gases in the feed (1). The fuel cell operating conditions that resulted in the greatest He purity were also identified (2). However, the effects of continuous operation for an extended duration on the fraction of H 2 removed by the PEMFC (i.e.…”
mentioning
confidence: 99%